Emotional Interventions A Study of Positive Visualization and Coping Strategies at the Elementary Level - Hutchison, Justin D. (My University, 2014)
This study sought to determine whether elementary school basketball players could improve their statistical performance through staff led emotional intervention training. A pre-experimental design was used for the study using a pre/post-test assessment strategy. The pre-tests/post-tests measured each student’s emotional intelligence level in athletics. Each player’s points, assists, and rebounds were examined before and after the emotional intervention training to determine if the training led to an increase in performance on the court. The treatment group received a one hour positive visualization training session once a week for a month. The topics discussed included mental toughness, emotion control, elimination of self-defeating thought, and positive visualization. The results of the post-test indicate there is no significant difference in basketball statistical performance between students who received emotional intervention training and students who did not receive the training.
Keywords: Education -- Research papers (Graduate); Basketball players -- Research; Emotional conditioning -- Research; School children -- Research